ChatGPT Enhances Programming Skills of Computer Engineering Students: https://doi.org/10.69692/SUJMRD100101 - Mekthanavanh, Vinath; Meksavanh, Bounhome; Bouddy, Somphong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research paper aims to outline the role of ChatGPT as one artificial intelligence technology that has progressed in depth and positive effect on the field of education and research with highly capable language developed by OpenAI. This technology presents an exciting opportunity for students and educators, including personalize feedback, increased ability accesses, lesson preparation, assessment and new way of teaching complexity such as code correction and completion, automatic syntax error fixing, code snippet suggestion, code refactoring suggestions and optimization, generate of missing code, document, text to code, and answering technical queries. The experimented was adopted with 51 students in final grade of Computer Engineering, Souphanouvong University and selected 30 students in interviews to collect data for analysis and evaluation. The results show that students with using ChatGPT to help in programming they can more understandable by able to explain, giving examples, concepts, technology of complex method, searching related information and technical solving problem, which can improve programming skills and careers in software development in the future. However, students are still concerned about the accuracy of information provided, loss personal interaction, data privacy issue and price.